Controlling the Boundaries of Morality: The History and Powers of Ayelala Deity - Oluwafunminiyi Raheem; Mike Famiyesin (Yoruba Studies Review)
The worship of deities has always been a major religious preoccupation among the Yoruba. Among these deities is Ayelala, a water goddess, who is not only worshiped with pomp and pageantry but also highly revered and respected for its judicial powers. As a deity of retribution and justice, Ayelala is believed to possess great powers which she uses against varying forms of social vice, such as armed robbery, sexual offences, and witchcraft to mention a few. Ayelala is reputed for seeking vengeance when the offender has forgotten her or his crime, and strikes her victims by inflicting on them bodily swelling and in few cases, dryness. Such is Ayelala’s overwhelming power and potency that the deity seeks to control the boundaries of morality and at the same time forms a major bulwark against societal impropriety.